Comparison of the Antioxidant Power of Extracts of the Red vs. Yellow Nephelium lappaceum Variety - Diaz Rojas, Mariana (2023)
Nephelium lappaceum L., also known as “Chinese mamon” (mamon chino) or “rambutan”, is an exotic fruit of tropical climate with a sweet flavor and aroma, which can be found in the territory of Costa Rica in the Brunca and Huetar Atlántica regions. For the comparison of antioxidants, different electronic tests were carried out with the red peel and the yellow peel of Nephelium lappaceum, taking ascorbic acid as a base. In addition, Nephelium lappaceum peels, due to their antioxidant properties, allowed the identification of the active components and their antioxidant activity by thin layer chromatography and DPPH tests. The results of these tests show the presence of flavonoids, coumarins, glycosides, and carotenoids, which are the primary metabolites of Nephelium lappaceum peels.